Relações entre o curso de Engenharia Agronômica do campus Sertão sergipano e a política pública da educação superior do campo - Carvalho, Jailda Evangelista do Nascimento (2019)
The present thesis deals with public policies on Higher Education in the Field and its main objective is to analyze the links and relations between Higher Education courses directed at rural workers in the perspective of rural education and Field Education in the context of the expansion of Higher Education, focusing on the historical construction of education at the Federal University of Sergipe (UFS). The study is guided by dialectical historical materialism. Therefore, it focuses on the knowledge of concrete reality about the creation of courses for rural workers since the implementation of the N. Sra. da Glória campus - UFS expansion project after REUNI. Therefore, we discuss the intentionality, challenges and perspectives found in the implementation process of these courses, with emphasis on the Agronomic Engineering course. It has as research sources: the documentary research and semi-structured interview with coordinators, teachers and students of the Course under analysis. Through the data collected, it was inferred that during successive governments, the policy of expansion of education was present, even though it was a majority in private institutions. With regard to higher education in the field, it is concluded that it is possible to consolidate an education policy focused on the context of the field as in the case of the course studied, but in order for it to materialize with quality, it is necessary to strengthen the public policy that guarantees access, permanence and quality of vocational training in the context of peasant work.________________________________________________________________________________________________________________________________